As múltiplas dimensões do risco para pessoas que convivem com inundações recorrentes: o caso de moradores da Vila América, Santo André/SP - Silva, Sandra Luzia Assis da (2016)
Our research analyses multiple dimensions of risk for people living with recurrent flooding in Vila América, Santo André/SP. To achieve our goals, the language of risks approach was used according to theoretical references developed in the Center for Studies and Research on Discursive Practices and Meaning Production (NEPPDS in Portuguese) at Pontifícia Universidade Católica de São Paulo (PUC/SP). Information was produced according to five main sources: 1) analyses of public documents; 2) field journals; 3) visits to the Civil Defence Department at the Municipal Service for Environmental Sanitation of Santo André (Semasa in Portuguese) and to Vila América; 4) semi-structured interviews with people who live in Vila América and 5) Photographs taken by residents and the researcher herself. Dialogic maps were used for analysis and interpretation. Information pro duced with this technic was gathered and counterpoised with specialized literature on risk. Results show that floods affect people socially, materially and economically, causing damages to physical and emotional health. Floods also highlight a structural problem in Brazil related to uncoordinated urbanization processes and fragile public policies, especially National Police for Civil Protection and Defence. To discuss the meaning of risk in daily life can contribute to overcame individualistic approaches to risk, traditionally applied to understand the ways people deal individually with risk in contemporary life. According to our research, the decision to move away or to stay in areas at risk of flooding is related to priorities people give to some risks instead of others. The process by which this hierarchy is produced depends on how people make sense of risks collectively. To understand how people give priority to certain risks instead of others is an option to i mprove preventive practices. Therefore, this research aims to give visibility to flood risk issues and civil rights violations at Vila América